Privacy in automation: An appraisal of the emerging Australian approach. Issue 6 (December 2017) - Daly, Angela
Abstract: This article presents an initial appraisal of the emerging Australian approach to applying privacy and data protection laws to automated technologies. These laws and the general context in which they operate will be explained, with appropriate comparisons made to the European Union frameworks. In order to examine their specific application vis-à-vis automated technologies, three case studies – automated facial recognition technologies (AFRT), unmanned aerial vehicles (UAVs – better known as 'drones') and autonomous vehicles (or 'driverless cars') – are selected to examine the extent to which existing privacy and data protection laws, and their application, can be considered adequate to address privacy and data protection risks that these technologies bring. These case studies evidence existing deficiencies with privacy protection in Australia and the inadequacy of recent reform processes, demonstrating that Australian data privacy laws are not well placed to protect individuals' rights vis-à-vis automated technologies.